International education, the formation of capital and graduate employment: Chinese accounting graduates' experiences of the Australian labour market. Issue 1 (2nd January 2017) - Blackmore, Jill; Gribble, Cate; Rahimi, Mark
Abstract : Since the late 1970s, international education has steadily gained in popularity in China. An emerging middle class seeks to strengthen its position in China's rapidly stratifying society under its socialist market economy with the shift from wealth creation for all to wealth concentration for a few. Previously, a foreign qualification was considered a passport to success in either the host or home country's labour market. But the growing popularity of overseas study, coupled with the massification of the Chinese higher education, means Chinese international students are seeking to distinguish themselves in an increasingly competitive global labour market. This longitudinal study of international graduates, backgrounded by Australian employer perceptions, examines the journeys of 13 Chinese accounting graduates as they attempt to transition from an Australian university into the Australian labour market. Bourdieu's thinking tools of field, capital, disposition and habitus are utilised to consider how different cultural, social and linguistic capitals inform employer understandings of 'employability' meant Chinese accounting graduates significantly adjusted their life goals.